2012
DOI: 10.1073/pnas.1204948109
|View full text |Cite
|
Sign up to set email alerts
|

Critical function for the Ras-GTPase activating protein RASA3 in vertebrate erythropoiesis and megakaryopoiesis

Abstract: Phenotype-driven approaches to gene discovery using inbred mice have been instrumental in identifying genetic determinants of inherited blood dyscrasias. The recessive mutant scat (severe combined anemia and thrombocytopenia) alternates between crisis and remission episodes, indicating an aberrant regulatory feedback mechanism common to erythrocyte and platelet formation. Here, we identify a missense mutation (G125V) in the scat Rasa3 gene, encoding a Ras GTPase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(71 citation statements)
references
References 36 publications
7
64
0
Order By: Relevance
“…The same studies identified the dual specificity GAP, RASA3, as the most abundant RAP-GAP expressed in platelets, with protein expression levels comparable to that of CalDAG-GEFI. An important confirmation that RASA3 may be a critical regulator of platelet function came from our findings that a G125V mutation in Rasa3 (Rasa3 scat ) is associated with severe thrombocytopenia in mice (33) and from recent studies by Molina-Ortiz et al, who described increased RAP1 activation in megakaryocytes from mice expressing a catalytically inactive mutant of RASA3 (34).…”
Section: Rasa3mentioning
confidence: 66%
See 2 more Smart Citations
“…The same studies identified the dual specificity GAP, RASA3, as the most abundant RAP-GAP expressed in platelets, with protein expression levels comparable to that of CalDAG-GEFI. An important confirmation that RASA3 may be a critical regulator of platelet function came from our findings that a G125V mutation in Rasa3 (Rasa3 scat ) is associated with severe thrombocytopenia in mice (33) and from recent studies by Molina-Ortiz et al, who described increased RAP1 activation in megakaryocytes from mice expressing a catalytically inactive mutant of RASA3 (34).…”
Section: Rasa3mentioning
confidence: 66%
“…Studies on the role of RASA3 in the activation response of human platelets are not possible currently, as specific inhibitors do not exist and patients with mutations in the gene have not been identified. Recent studies in mice demonstrated that expression of RASA3 mutants leads to high embryonic lethality and severe thrombocytopenia (33,34). To test whether the embryonic lethality of Rasa3 mutant mice is caused by defective platelet function, we deleted Rasa3 both systemically (Rasa3 Figure 1D), including cutaneous and jugular lymphatics and the thoracic duct (Supplemental Figure 2), in which platelets and the lymphovenous valve are required to prevent backflow of blood into the lymphatic vasculature (36).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One is the Ras-GTPase activating protein Rasa3, which when mutated in Scat mice leads to anemia and thrombocytopenia. 56 A second is neurofibromin (Nf1), for which mutations have been associated with juvenile myelomonocytic leukemia, including anemia due to limited EPC differentiation. 57 Regulation of RAS-modulated targets is also important for EPOdependent erythropoiesis.…”
Section: Epor Signal Transduction Via Rat Sarcoma/ Mek Kinase/mitogenmentioning
confidence: 99%
“…47 Important downstream EPOR signal transducers are also being discovered ( Figure 1C). Within a central RAS/MEK module, these include MASL1, 63 Rasa3, 56 and neurofibrin, 57 that act to balance ERK1/2 signaling and EPC production. For EPC cytoprotection, an EPO-induced Spi2A serpin and small molecule inhibitors of leached lysosomal cathepsins have emerged that lessen ROSassociated damage.…”
mentioning
confidence: 99%